2022
DOI: 10.1002/celc.202201052
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the FAA3‐50 Polymer Electrolyte for Anion Exchange Membrane Fuel Cells

Abstract: AEMFC is an attractive alternative to PEMFCs, due to the faster reaction kinetics that permits to use non‐platinum‐group metal catalysts and thanks to the high pH of the electrolyte allows less expensive metal hardware. In any case, the use of an alkaline exchange polymeric membrane as an electrolyte requires the development and optimization of the electrode structures and MEA. In this work, MEAs, based on FAA3‐50 commercial membrane, were developed and electrochemically characterized in single cell configurat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Despite the simplicity of this ion-exchange step, significant performance differences have been reported with small variations of this procedure. For example, Gatto et al tested the performance of an AEMFC with Fumatech FAA-3 ionomer and membrane, by varying the ion-exchange time in alkaline solution (1 m KOH) from 1 to 24 h. [56] They found that in the first case, the fuel cell performed better, with a cell potential of 0.656 V@ 200 mA cm −2 , compared to 0.460 V for the second case. This could indicate that the membrane is subject to alkaline degradation, and prolonged exchange times weaken the membrane structure.…”
Section: A Note On Ion Exchange For Commercial Aeismentioning
confidence: 99%
“…Despite the simplicity of this ion-exchange step, significant performance differences have been reported with small variations of this procedure. For example, Gatto et al tested the performance of an AEMFC with Fumatech FAA-3 ionomer and membrane, by varying the ion-exchange time in alkaline solution (1 m KOH) from 1 to 24 h. [56] They found that in the first case, the fuel cell performed better, with a cell potential of 0.656 V@ 200 mA cm −2 , compared to 0.460 V for the second case. This could indicate that the membrane is subject to alkaline degradation, and prolonged exchange times weaken the membrane structure.…”
Section: A Note On Ion Exchange For Commercial Aeismentioning
confidence: 99%
“…The reason we put deionized water and catalyst in the first place is that if we pour the ethanol directly onto the platinum, it will flare up. Mixing was carried out in an ultrasonic bath [10,13,14].…”
Section: Preparation Of Inkmentioning
confidence: 99%
“…This highlights the significance of optimizing ion exchange durations for stronger Anion Exchange Membrane Water Electrolysis (AEMWE) membranes and enhanced MEA efficiency. [13]. Using the catalyst-coated membrane method with the FAA3-50 membrane enables operation at higher temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Fumasep electrolytes consist of an aminated poly(phenylene oxide) backbone with quaternary ammonium groups [ 18 ] and find use in various applications, including hydrogen production by electrolysis of water [ 19 ], electrodialysis [ 20 ] and acid regeneration [ 21 ]. However, relatively few works have investigated the use of Fumasep membranes in AEMFC MEA [ 22 , 23 , 24 , 25 ] and the use of platinum-based cathodic and anodic catalysts when forming MEA.…”
Section: Introductionmentioning
confidence: 99%